# If f ( x ) = 4 x 2 − 2 x + 3 f ( x ) = 4 x 2 – 2 x + 3 , find f ‘ ( − 5 ) f ′ ( – 5 ) . Use this to find the equation of the tangent line to the parabola y = 4 x 2 − 2 x + 3 y = 4 x 2 – 2

If

f

(

x

)

=

4

x

2

−

2

x

+

3

f

(

x

)

=

4

x

2

–

2

x

+

3

, find

f

‘

(

−

5

)

f

′

(

–

5

)

.

Use this to find the equation of the tangent line to the parabola

y

=

4

x

2

−

2

x

+

3

y

=

4

x

2

–

2

x

+

3

at the point

(

−

5

,

113

)

(

–

5

,

113

)

. The equation of this tangent line can be written in the form

y

=

m

x

+

b

y

=

m

x

+

b

where

m

m

is:

and where

b

b

is: